Economics of Labour Use in Selected Food Crop Farming in Ogun State, Nigeria - Adewuyi , S. A; Fapojuwo , O. E; Sowemimo , S. H (Asian Journal of Agriculture and Rural Development, 2014)
The study evaluates economic analysis of labour use in food crops production in Ogun state, Nigeria. Data were collected by the use of multistage random sampling with the help of well-structured questionnaire from a cross-section of 170 Food crop farmers and analysed using descriptive, budgetary and multiple regression. The socio-economic data of the respondents were analysed by descriptive statistics and the result revealed that majority (82.4%) of the food crop farmers were male, aged between 41 and 60 years. The mean household size was 4 persons. The mean farm size was 1.8ha with a mean farming experience of 25years. The result of the budgetary analysis reveals that for a hectare of farmland, a cost of N213, 60766 was incurred giving a revenue of N 352,809.59 and a rate of investment (ROI) of 0.65. This shows for every N1 spent, there was corresponding profit of 65kobo. The study further revealed that farm size, labour (man-day) and cost of plant material significantly influence the revenue of farmers in the study area. The study concludes that food crop production is profitable but at a high cost of labour. The study recommends the adoption of labour savings technology as an alternative to increasing scarcity and high labour cost in the study area.